Sowing the seeds of stereotypes spontaneous inferences about groups. [article]. - Hamilton, David L.; Chen, Jacqueline M.
Although dispositional inferences may be consciously drawn from the trait implications of observed behavior, abundant research has shown that people also spontaneously infer trait dispositions simply in the process of comprehending behavior. These spontaneous trait inferences (STIs) can occur without intention or awareness. All research on STIs has studied STIs based on behaviors of individual persons. Yet important aspects of social life occur in groups, and people regularly perceive groups engaging in coordinated action. We propose that perceivers make spontaneous trait inferences about groups (STIGs), parallel to the STIs formed about individuals. In 5 experiments we showed that (a) perceivers made STIGs comparable with STIs about individuals (based on the same behaviors), (b) a cognitive load manipulation did not affect the occurrence of STIGs, (c) STIGs occurred for groups varying in entitativity, (d) STIGs influenced perceivers' impression ratings of those groups, and (e) STIG-based group impressions generalized to new group members. These experiments provide the first evidence for STIGs, a process that may contribute to the formation of spontaneous group impressions. Implications for stereotype formation are discussed. -- (from the authors)